HALAL TOURISM POTENTIAL, CHALLENGES, AND DEVELOPMENT STRATEGIES AT JATIMPARK 2, MALANG CITY - Jannah, Novita Lailatul (PERCIPIENCE International Journal of Social, Administration, & Entrepreneurship, 2024)
Halal tourism is a rapidly growing tourism segment globally, driven by the increasing number of Muslim tourists. Indonesia has a significant opportunity to optimize the halal tourism market, including in man-made tourist destinations like Jatim Park 2 in Malang City. This study aims to analyze the potential, challenges, and strategies for developing halal tourism at Jatim Park 2 in Malang City. The research approach used was descriptive-qualitative, with data collection techniques including observation, in-depth interviews with managers, local government officials, and Muslim tourists, and documentation. The results indicate that Jatim Park 2 has significant potential as a halal tourism destination due to its strategic location, large Muslim market segment, and educational tourism theme aligned with Islamic values. However, several challenges remain, including the lack of halal certification for food court tenants, suboptimal prayer room facilities, a lack of human resource understanding of the halal tourism concept, and the absence of halal tourism branding in destination promotions. Based on the SWOT analysis, potential strategies for halal tourism development include optimizing prayer facilities, facilitating halal certification for food tenants, training human resources on halal tourism, strengthening halal tourism branding, and developing halal tourism education programs. This study recommends collaboration between Jatim Park 2 management, the local government, halal certification bodies, and the community to develop Jatim Park 2 as a leading halal tourism destination in East Java.